2020
DOI: 10.1073/pnas.1909943117
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal gating of SIRT1 functions by O-GlcNAcylation is essential for liver metabolic switching and prevents hyperglycemia

Abstract: Inefficient physiological transitions are known to cause metabolic disorders. Therefore, investigating mechanisms that constitute molecular switches in a central metabolic organ like the liver becomes crucial. Specifically, upstream mechanisms that control temporal engagement of transcription factors, which are essential to mediate physiological fed–fast–refed transitions are less understood. SIRT1, a NAD+-dependent deacetylase, is pivotal in regulating hepatic gene expression and has emerged as a key therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 77 publications
4
37
0
Order By: Relevance
“…Sirtuin 1 (Sirt1) is an energy sensor that regulates metabolism across tissues 14,15 . Activation or overexpression of Sirt1 improves systemic metabolism and protects against diabetes, obesity, or high-fat diet-induced metabolic damages [16][17][18][19][20][21][22] , while dysregulated Sirt1 resulted in phenotypes associated with diabetes, obesity, and aging 23 . In adipocytes, upregulation of Sirt1 enhances lipolysis and attenuates adipogenesis 24 , and ablation of Sirt1 promotes adipocyte differentiation and increases adiposity in mice 25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…Sirtuin 1 (Sirt1) is an energy sensor that regulates metabolism across tissues 14,15 . Activation or overexpression of Sirt1 improves systemic metabolism and protects against diabetes, obesity, or high-fat diet-induced metabolic damages [16][17][18][19][20][21][22] , while dysregulated Sirt1 resulted in phenotypes associated with diabetes, obesity, and aging 23 . In adipocytes, upregulation of Sirt1 enhances lipolysis and attenuates adipogenesis 24 , and ablation of Sirt1 promotes adipocyte differentiation and increases adiposity in mice 25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…Others and we have found that metabolic cues under fasting conditions elicit anticipatory molecular mechanisms to mount an efficient fed response (Chattopadhyay et al, 2020;Maniyadath et al, 2019;Shaw et al, 2020). Given that fasting insulin (0.1nM) is pulsatile with a frequency of 10-15min, our findings have shown that this rewires fed IS dynamics.…”
Section: Discussionmentioning
confidence: 67%
“…We have found that leytragin promoted SIRT1 mRNA transcription in the lungs of LPS-induced mice. We did not measure SIRT1 protein levels, since the SIRT1 protein undergoes rapid degradation in the fed state via the ubiquitin-proteasome pathway [ 38 ] (all animals in our study had free access to food over the 72-hour period of observation). Thus, the upregulation of SIRT1 expression appears to be the mechanism by which leytragin shifts the acetylation-deacetylation balance toward HMGB1 deacetylation, thereby preventing HMGB1 release in LPS-induced mice.…”
Section: Discussionmentioning
confidence: 99%